Characteristics of plasma sheath in multi-component plasmas with three-ion species - M. M. Hatami (Scientific Reports, 2022)
Abstract The plasma sheath of a three ion species plasma is studied numerically, relying on the results of the experiment by Yip et al. (Phys. Plasmas 23:050703 (2016) to measure the positive ion velocities at the sheath edge. The positive ion species ( $$Ar^+$$ A r + , $$Kr^+,$$ K r + , and $$Xe^+$$ X e + ) are assumed to be singly charged and to be characterized by the same temperature. It is shown that the sheath characteristics, viz. the particle number densities, the electrostatic potential and the space charge density profile in the sheath all depend on the $$Kr^+$$ K r + concentration that is gradually added to the argon-xenon plasma as the third positive ion species. Also, the effect of ion-neutral collisions on the sheath properties is investigated numerically. Our results may be extended to a multi-ion plasma with more than two species of positive ions.